RETRACTED ARTICLE: GPX8 is transcriptionally regulated by FOXC1 and promotes the growth of gastric cancer cells through activating the Wnt signaling pathway - Hong Chen; Lu Xu; Zhi-li Shan; Shu Chen; Hao Hu (Cancer Cell International, 2020)
Abstract Background Glutathione Peroxidase 8 (GPX8) as a member of the glutathione peroxidase (GPx) family plays an important role in anti-oxidation. Besides, dysregulation of GPX8 has been found in gastric cancer, but its detailed molecular mechanism in gastric cancer has not been reported. Methods Our study detected the expression of GPX8 in gastric cancer tissues and cell lines using immunohistochemistry (IHC), western blot and qRT-PCR, and determined the effect of GPX8 on gastric cancer cells using CCK-8, colony formation, transwell migration and invasion assays. Besides, the effect of GPX8 on the Wnt signaling pathway was determined by western blot. Furthermore, the transcription factor of GPX8 was identified by bioinformatics methods, dual luciferase reporter and chromatin immunoprecipitation (CHIP) assays. In addition, the effect of GPX8 on tumor formation was measured by IHC and western blot. Results The over-expression of GPX8 was observed in gastric cancer tissues and cells, which facilitated the proliferation, migration and invasion of gastric cancer cells as well as the tumor growth. GPX8 knockdown effectively inhibited the growth of gastric cancer cells and tumors. Moreover, GPX8 could activate the Wnt signaling pathway to promote the cellular proliferation, migration and invasion through. Furthermore, FOXC1 was identified as a transcription factor of GPX8 and mediated GPX8 expression to affect cell development processes. Conclusions These findings contribute to understanding the molecular mechanism of GPX8 in gastric cancer. Additionally, GPX8 can be a potential biomarker for gastric cancer therapy.